2010
DOI: 10.1186/1477-7827-8-116
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of CD25+CD4+ and FOXP3+ regulatory T cells in ectopic endometrium and ectopic decidua

Abstract: BackgroundThe presence of regulatory T (Treg) cells in human endometrium is crucial for maintaining immunological homeostasis within the uterus. For this study we decided to evaluate the subpopulations of Treg cells in conditions where a disturbance in the immunological equilibrium in ectopic endometrium and decidua has been observed, such as in cases of ovarian endometriosis (involving local immune cell suppression) and ectopic pregnancy (involving an increase in local immune system activity). We then compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 40 publications
7
41
0
3
Order By: Relevance
“…The increase in the number of Treg cells depends on estrogen (E) levels, and Es are also responsible for the increase in the immune suppressive potential of these cells (18). Estrogen levels generally seem to be linked with a decrease in TH1 response and the absence of Treg cell fluctuation can be linked to an immune defect arising with the development of endometriosis (17,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the number of Treg cells depends on estrogen (E) levels, and Es are also responsible for the increase in the immune suppressive potential of these cells (18). Estrogen levels generally seem to be linked with a decrease in TH1 response and the absence of Treg cell fluctuation can be linked to an immune defect arising with the development of endometriosis (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…The specific activities of these immune cells are crucial for the proper course of such reproductive processes as menstruation and implantation (16). An alteration in Treg lymphocyte infiltration generally disrupts the immunologic equilibrium (17). The increase in the number of Treg cells depends on estrogen (E) levels, and Es are also responsible for the increase in the immune suppressive potential of these cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…Specific activities of these cells are crucial for an appropriate course of reproductive processes, such as menstruation and implantation (33). Changes in lymphocyte infiltration of Tregs may disturb the immune balance (34), damaging these processes.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Treg cells has also been correlated with poor prognosis in ovarian cancers [ 83 ]. The presence of Treg cells in eutopic and ectopic endometrium in endometriosis has been documented [ 84 ]. One study found increased Treg cells in the peritoneal fl uid and decreased levels in the peripheral blood of women with endometriosis compared to controls without endometriosis.…”
Section: Immunologymentioning
confidence: 97%